The Influence of Workplace Spirituality in Engagement, Resilience and Efficacy of Secondary Teachers in Iba District, Schools Division of Zambales - Fulgencio, Shiela Marie R. (Future Science / FSH-PH Publications, 2025)
This study examined the relationship between workplace spirituality and engagement, resilience, and self-efficacy among secondary school teachers in Iba District, Schools Division of Zambales, during the 2018-2019 school year. A descriptive research design was used, employing a questionnaire to gather data from 138 randomly selected teachers. The study explored workplace spirituality through compassion, meaningful work, mindfulness, and transcendence, alongside teacher attributes such as engagement, resilience, and self-efficacy. It also considered respondents' age, sex, religion, civil status, educational attainment, and years of service. Findings revealed that most respondents were 33 years old, female, Catholic, married, held a BS degree with MA units, and had seven years of teaching experience. Workplace spirituality, particularly compassion, mindfulness, and transcendence, was perceived as occurring